2016
DOI: 10.1007/s11270-016-2778-2
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Copper Concentrations, In Situ Benthic Invertebrate Abundance, and Sediment Toxicity: Comparison of Treated and Untreated Coves in a Southern Reservoir

Abstract: Copper-based algaecides are used to control algae that compromise uses of lakes and reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Except for one cove that received a recent treatment, no difference in sediment total copper concentrations was measured in treated and untreated coves in Lay Lake. In situ benthic invertebrate abundance was also not significantly different between treated and untreated coves (Iwinski et al 2016). Additionally, all treated coves tested have similar or increased survival of Chironomus dilutus and Hyalella azteca in sediment toxicity tests with sampled sediment at different points in time (Calomeni et al 2015;Iwinski et al 2016).…”
Section: Risk Assessment Of Programsmentioning
confidence: 83%
See 2 more Smart Citations
“…Except for one cove that received a recent treatment, no difference in sediment total copper concentrations was measured in treated and untreated coves in Lay Lake. In situ benthic invertebrate abundance was also not significantly different between treated and untreated coves (Iwinski et al 2016). Additionally, all treated coves tested have similar or increased survival of Chironomus dilutus and Hyalella azteca in sediment toxicity tests with sampled sediment at different points in time (Calomeni et al 2015;Iwinski et al 2016).…”
Section: Risk Assessment Of Programsmentioning
confidence: 83%
“…In situ benthic invertebrate abundance was also not significantly different between treated and untreated coves (Iwinski et al 2016). Additionally, all treated coves tested have similar or increased survival of Chironomus dilutus and Hyalella azteca in sediment toxicity tests with sampled sediment at different points in time (Calomeni et al 2015;Iwinski et al 2016). Short-term laboratory toxicity studies on sentinel aquatic organisms showed that components of Program 1 may have some impact to larval fish or invertebrates (Johnson et al 2008;Calomeni et al 2015).…”
Section: Risk Assessment Of Programsmentioning
confidence: 83%
See 1 more Smart Citation
“…band treatments), due to dilution and lateral copper movement. A study by Iwinski et al [27] comparing coves treated ~5 times a year for up to 10 years indicated that a majority of the sites had similar copper concentrations as adjacent untreated coves (p = 0.77, α = 0.05; treated n = 27, mean = 51.6 mg Cu/kg; untreated n = 27, mean = 151.3 mg Cu/kg). In circumstances of repeated or large treatment areas (e.g.…”
Section: Copper Fate From Aquatic Pesticide Applicationsmentioning
confidence: 99%
“…Willis [28] found the copper bioavailability in sediments from an aquaculture pond collected three weeks following a chelated copper algaecide application was inadequate to elicit adverse effects to Hyalella azteca. Iwinski et al [27] found that coves in a lake treated ~5 times a year for up to 10 years lacked measurable adverse effects based on laboratory toxicity experiments and in situ benthic abundance data.…”
Section: Copper Bioavailability and Non-target Risksmentioning
confidence: 99%